MEMBANGUN DAYA SAING SISWA SMK MELALUI OPTIMALISASI EMPLOYABILITY SKILL DAN KOMPETENSI - Hakim, Dani Rahman; Fitri, Euis Nessia (Prodi Teknologi Pendidikan, 2020)
This study aims to : 1) analyzing the effect of learning achievement, ICT Skills, and industrial work practices (internship) on studet competencies, 2) analizing the effect of learning achievement, ICT Skills, internship, and competencies on employability skills, and 3) analizing the effect of learning achievement, ICT Skills, internship, competencies, and employability skill on competitiveness of vocational students in Accounting Department in South Tangerang City. Total sample on this research is 284 students. Analizing data method is used the quantitative approach with path analisys. The results of this research include: 1) learning achievement has a positive and significant effect on competence, ICT Skill has no effect on competence, and internship has a negative and significant effect on competence. 2) learning achievement and ICT Skill did not significantly affecting employability skills, whereas Internship and competence had a positive and significant effect on employability skills. 3) learning achievement, ICT Skill, Internship, and Competence did not significantly affect competitiveness, while employability skills had a positive and significant effect on competitiveness. Based on these results, it can be understood that until now competence has not been able to be a determining factor in increasing student competitiveness. On that basis, the government should be developing a new formula that can be encouraging vocational schools to developing their students competenceâ€™s and employability skills.Â Penelitian ini bertujuan untuk : 1) menganalisis pengaruh prestasi belajar, ICT Skills, dan praktik kerja industri (magang) terhadap kompetensi mahasiswa, 2) menganalisis pengaruh prestasi belajar, ICT Skills, magang, dan kompetensi terhadap Employability skills, dan 3 ) menganalisis pengaruh prestasi belajar, Keterampilan ICT, magang, kompetensi, dan keterampilan kerja terhadap daya saing siswa SMK di Jurusan Akuntansi di Kota Tangerang Selatan. Jumlah sampel dalam penelitian ini adalah 284 siswa. Metode analisis data yang digunakan adalah pendekatan kuantitatif dengan analisis jalur. Hasil penelitian ini antara lain: 1) prestasi belajar berpengaruh positif dan signifikan terhadap kompetensi, ICT Skill tidak berpengaruh terhadap kompetensi, dan magang berpengaruh negatif dan signifikan terhadap kompetensi. 2) Prestasi belajar dan ICT Skill tidak berpengaruh signifikan terhadap Employability Skill, sedangkan Magang dan Kompetensi berpengaruh positif dan signifikan terhadap Employability Skill. 3) Prestasi belajar, Keterampilan TIK, Magang, dan Kompetensi tidak berpengaruh signifikan terhadap daya saing, sedangkan keterampilan kerja berpengaruh positif dan signifikan terhadap daya saing. Berdasarkan hasil tersebut dapat dipahami bahwa sampai saat ini kompetensi belum mampu menjadi faktor penentu dalam meningkatkan daya saing mahasiswa. Atas dasar itu, pemerintah harus mengembangkan formula baru yang dapat mendorong sekolah kejuruan untuk mengembangkan kompetensi dan keterampilan kerja siswanya.